Admission risk factors and predictors of moderate or severe pediatric acute pancreatitis: A systematic review and meta-analysis - Márk Félix Juhász; Márk Félix Juhász; Zoltán Sipos; Klementina Ocskay; Péter Hegyi; Péter Hegyi; Péter Hegyi; Péter Hegyi; Anikó Nagy; Andrea Párniczky; Andrea Párniczky; Andrea Párniczky (Frontiers Media S.A., 2022)
IntroductionPediatric acute pancreatitis (PAP) has an increasing incidence and is now estimated to be almost as common as in adults. Up to 30% of patients with PAP will develop moderate or severe disease course (M/SPAP), characterized by organ failure, local or systemic complications. There is still no consensus regarding on-admission severity prediction in these patients. Our aim was to conduct a systematic review and meta-analysis of available predictive score systems and parameters, and differences between on-admission parameters in mild and M/SPAP.MethodsWe conducted a systematic search on the 14th February, 2022 in MEDLINE, Embase and CENTRAL. We performed random-effects meta-analysis of on-admission differences between mild and M/SPAP in laboratory parameters, etiology, demographic factors, etc. calculating risk ratios (RR) or mean differences (MD) with 95% confidence intervals (CI) and created forest plots. For the meta-analysis of predictive score systems, we generated hierarchical summary receiver operating characteristic curves using a bivariate model. Chi-squared tests were performed and I2 values calculated to assess statistical heterogeneity.ResultsWe included 44 studies - mostly retrospective cohorts - in our review. Among predictive score systems examined by at least 5 studies, the modified Glasgow scale had the highest specificity (91.5% for values ≥3), and the Pediatric Acute Pancreatitis Severity score the highest sensitivity (63.1% for values ≥3). The performance of other proposed score systems and values were summarized. Traumatic (RR: 1.70 95% CI: 1.09-2.67) and drug-induced (RR: 1.33 95% CI: 0.98-1.87) etiologies were associated with a higher rate of M/SPAP, while anatomical (RR: 0.6195% CI: 0.38-0.96) and biliary (RR: 0.72 95% CI: 0.53-0.99) PAP tended to be less severe.DiscussionMany predictive score systems were proposed to assess the possibility of M/SPAP course. The most commonly used ones exhibit good specificity, but subpar sensitivity. Our systematic review provides a rigorous overview of predictive options assessed thus far, that can serve as a basis for future improvement of scores via the addition of parameters with a better observed sensitivity: e.g., lipase exceeding 7-times the upper threshold, hemoglobin, etc. The addition of etiological factors is another possibility, as they can herald a more severe disease course.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?RecordID=307271, PROSPERO, identifier: CRD42022307271.